TiO2(R)/VO2(M)/TiO2(A) multilayer film as smart window: Combination of energy-saving, antifogging and self-cleaning functions. (January 2015) - Zheng, Jianyun; Bao, Shanhu; Jin, Ping
Abstract: A novel Multifunctional TiO2 (R)/VO2 (M)/TiO2 (A) multilayer film is designed and deposited by medium frequency reactive magnetron sputtering. An exciting fact that the antifogging, self-cleaning and energy-saving effects are integrated into the multilayer film could offer significant potential for wider applications of smart window. Thereinto, the bottom TiO2 layer with rutile phase plays an important role in the formation of monoclinic phase of VO2 layer and serves as an antireflection layer. Then, the VO2 layer with dominant monoclinic phase performs an automatic solar/heat control for saving energy. Finally, the top TiO2 layer containing a mixed phase of anatase and rutile displays the remarkable photocatalytic and photoinduced properties. According to optical tests, the multilayer film shows satisfactory optical properties with an excellent solar regulation efficiency (Δ T sol =10.2%) and an applicable luminous transmittance ( T lum-L =30.1%) in a low-temperature state. In addition, the multilayer film implements a photoinduced super-hydrophilicity (~ 2.1°) through UV-irradiation, resulting in an antifogging effect. A high level of photocatalytic activity is detected on the surface of the multilayer film through degradation of stearic acid and rhodamine B. Graphical abstract: Highlights: Multifunctional TiO2 /VO2 /TiO2 multilayer film was designed and prepared. Multilayer film had an excellent solar regulation efficiency and an applicable luminous transmittance. The film implemented a photoinduced super-hydrophilicity resulting in an antifogging effect. Meanwhile, a high level of photocatalytic activity was detected on the surface of the multilayer film.